The Influence of the Instantaneous Collapse of Tailings Pond on Downstream Facilities - Sha Wang; Guodong Mei; Xuyang Xie; Lijie Guo (Advances in Civil Engineering)
To evaluate the evolutionary processes guiding the formation of the tailings-water mixtures produced by the instantaneous collapse of tailings ponds and the influence of these on downstream facilities, a 2D simulation model with reasonable boundary and working conditions derived from actual engineering practice was built in this study, and the relationship between dam-break elevation and impact on downstream facilities was also analyzed to determine the relevant mechanism of influence. Computational results indicated that lowering the dam-break elevation caused the maximum velocity and flooding depth, along with the flooded area at monitoring points, to gradually increase. The occurrence times of maximum velocity and flooding depth were also gradually moved forward as the breaking elevation was reduced; this effect is directly related to the increase in the total potential energy at the lower break elevations. Further simulations of sand-prevent dams with different heights located downstream from a tailings pond were carried out to identify methods for mitigating the impact of dam failure. The results revealed that increasing the height of the sand-prevent dam reduced the production of tailings mixtures. Based on the results, the construction of a sand-prevent dam with a crest elevation equal to that of the starter dam was recommended.